Evaluation of streptococcal toxic shock-like syndrome caused by group B streptococcus in adults in Japan between 2009 and 2013. Issue 3 (March 2015) - Ikebe, Tadayoshi; Chiba, Kazuki; Shima, Tomoko; Masuda, Chieko; Okuno, Rumi; Ohya, Hitomi; Ogata, Kikuyo; Katsukawa, Chihiro; Kawahara, Ryuji; Tominaga, Kiyoshi; Yabata, Junko; Tada, Yuki; et al.
Abstract: Infection with Streptococcus agalactiae has long been recognized in infants. In recent years, S. agalactiae is an important cause of morbidity and mortality among adults and among those with underlying medical condition. Several cases of GBS infection and more fulminant disease similar to streptococcal toxic shock syndrome have recently been reported. We report here that 19 S. agalactiae strains were isolated from streptococcal toxic shock-like syndrome cases involving adult patients in Japan between 2009 and 2013. The average age of the patients was 66.3 years. At least one underlying disease was present in 47.4% (9/19) of the patients. The most prevalent serotype among these strains was Ib. All serotype Ib strains belonged to clonal complex 10 and were ciprofloxacin resistant. In contrast, all strains were susceptible to penicillin G, ampicillin, cefazolin, cefotaxime, imipenem, panipenem, and linezolid. The characteristic type distributions of streptococcal toxic shock-like syndrome isolates differed between isolates obtained from vaginal swabs of women and infants with invasive infections.